2019
DOI: 10.2478/raft-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Intercultural Competence of Military Students in the Context of International Mobility

Abstract: This study aims to evaluate intercultural competence for military students before they go on an international mobility stage and after its completion, in order to see if intercultural competence is formed in real intercultural contexts. In the study, we addressed both theoretical and practical aspects of intercultural competence. As an instrument for data collection, an intercultural competency assessment questionnaire was used and, following its application, it was found that the high level of the “knowledge”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to those mentioned by us in another study that also included military students, this competence can be the key to integration in various cultures (Matei, 2019;Matei & Lincă, 2019). Deardorff (2006) argued that this competence consists of three main elements: knowledge, skills, and attitudes.…”
Section: Introductionmentioning
confidence: 92%
“…According to those mentioned by us in another study that also included military students, this competence can be the key to integration in various cultures (Matei, 2019;Matei & Lincă, 2019). Deardorff (2006) argued that this competence consists of three main elements: knowledge, skills, and attitudes.…”
Section: Introductionmentioning
confidence: 92%
“…Languages, cultural and social awareness are some of the more frequently referred employability skills enhanced by the Erasmus program (Mattern, 2016). During an international mobility exchange, students face intercultural challenges when interacting with people from different cultures providing the opportunity to enhance their intercultural skills (Matei, 2019). Besides, it has also been suggested that the mobility programme increases students' cosmopolitan orientation, European consciousness and identity (Jacobone & Moro, 2015) and it could also be an excellent way for students to learn more about host countries social and economic reality (Cairns, 2017).…”
Section: Development Of Skills Related To the Erasmus Experiencementioning
confidence: 99%
“…I started to pay attention to this topic since 2019 when I carried out several studies regarding the importance of intercultural competence for students in the context of international mobility. Two of the studies carried out on this topic targeted military students (Matei, 2019, 2020, Matei, Lincă, 2019. Thus, we identified perceptions and training needs of students, but also the existence of correlations between the components of intercultural competence.…”
Section: Introductionmentioning
confidence: 99%